Serological Investigation of Japanese Encephalitis Virus Infection in Commercially Reared Pigs, Southwestern Nigeria - Adeleke, Richard; Olanipekun, Tobi; Abiola, John; Aluko, Adegboyega; Sule, Waidi; Oluwayelu, Daniel (Veterinaria Italiana, 2023)
Japanese encephalitis virus (JEV) is a zoonotic arbovirus that causes abortion, stillbirth, and congenital defects in pigs, and epidemic encephalitis in humans. Currently, there is scarcity of information on JEV infection in pigs in Nigeria. Since the Culex tritaeniorhynchus vector of JEV is present in Nigeria and considering recent anecdotal reports of abortions and birth of weak piglets in some pig farms in southwestern Nigeria, there is a need for studies on the presence of the virus and its true burden among pig populations in the country. Serum samples (n=368) obtained from farm-reared pigs in four States of southwestern Nigeria were screened for JEV-specific IgG antibodies using a commercial ELISA kit. An overall JEV seropositivity of 35.1% (95% CI: 30.18 – 39.93%) was obtained, with detectable antibodies in pigs of all age groups, breeds, sex, and locations. Our results suggest natural exposure of these unvaccinated intensively reared pigs to JEV circulating silently in the swine population with significant association of the seropositivity with location (state/community in which the pig farms exist) and breed of the pigs studied. This first report of detection of anti-JEV antibodies in pigs in Nigeria indicates that JEV circulated among these pigs and underscores the need for active surveillance for JEV in humans, pigs, and mosquitoes to provide valuable epidemiological data for the design of effective control strategies against the virus, thus forestalling potential future outbreaks of the infection.